A multi-objective differential evolutionary algorithm for constrained multi-objective optimization problems with low feasible ratio - Yang, Yongkuan; Liu, Jianchang; Tan, Shubin; Wang, Honghai (Applied soft computing, 2019)
Most current evolutionary multi-objective optimization (EMO) algorithms perform well on multi-objective optimization problems without constraints, but they encounter difficulties in their ability for constrained multi-objective optimization problems (CMOPs) with low feasible ratio. To tackle this problem, this paper proposes a multi-objective differential evolutionary algorithm named MODE-SaE based on an improved epsilon constraint-handling method. Firstly, MODE-SaE self-adaptively adjusts the epsilon level in line with the maximum and minimum constraint violation values of infeasible individuals. It can prevent epsilon level setting from being unreasonable. Then, the feasible solutions are saved to the external archive and take part in the population evolution by a co-evolution strategy. Finally, MODE-SaE switches the global search and local search by self-switching parameters of search engine to balance the convergence and distribution. With the aim of evaluating the performance of MODE-SaE, a real-world problem with low feasible ratio in decision space and fourteen bench-mark test problems, are used to test MODE-SaE and five other state-of-the-art constrained multi-objective evolution algorithms. The experimental results fully demonstrate the superiority of MODE-SaE on all mentioned test problems, which indicates the effectiveness of the proposed algorithm for CMOPs which have low feasible ratio in search space. •To solve constrained multi-objective optimization problems with low feasible ratio.•An algorithm based on an improved epsilon constraint-handling method is proposed.•A co-evolution strategy of the external archive is used to save feasible solutions.•Our algorithm self-switches parameters of DE to balance convergence and distribution.•Our algorithm provides an effective tool to solve the above problems.